KONTRIBUSI PONDOK PESANTREN DALAM MEMBENTUK KARAKTER SANTRI - Safitri, Anita; Muhtarom, H.Ali; Marzuki, Ahmad; Mubarok, Achmat (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2024)
Islamic Boarding Schools is the oldest Islamic education institution in Indonesia, with efforts to increase the morale of students. Baiturrahman Islamic Boarding School contributes to shaping the character of the students by acting as a). maintainer of Islamic culture b). training of prospective scholars. So that this contribution fosters the character values ​​of the santri, including: humility, independence, tolerance, peace-loving, cooperation, deliberation, responsibility, patience and concern. Baiturrahman Islamic Boarding School also has supporting factors and inhibiting factors in shaping the character of the students. Supporting factors include internal factors from within the students themselves and external factors from the community environment. While the inhibiting factors of the Baiturrahman Islamic Boarding School are also from within the students themselves and the community environment as well as the facilities of the Islamic boarding school.